2022
DOI: 10.1186/s12889-022-13486-1
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic inequalities in health service utilization among Chinese rural migrant workers with New Cooperative Medical Scheme: a multilevel regression approach

Abstract: Background While reducing inequity in health service utilization is an important goal of China’s health system, it has been widely acknowledged that a huge number of rural migrant workers cannot be effectually protected against risks with the New Rural Cooperative Medical Insurance (NCMS). Method Data of the 2016 China Labor-force Dynamic Survey and the Chinese Urban Statistical Yearbook were used. The multilevel regression approach was implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In addition, this study found that migrant women had a lower vaccination rate of RV and were more prone to have a past infection of RV by natural ways. Previous studies have reported the insufficient utilization of health care services among migrants than general populations due to restrictive health-related policies, poor economic conditions, and the lack of awareness of seeking medical services [ 36 , 37 ]. Migrants were often overlooked for the RV vaccine catch-up immunization programs and their immunity was often acquired by natural infection [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study found that migrant women had a lower vaccination rate of RV and were more prone to have a past infection of RV by natural ways. Previous studies have reported the insufficient utilization of health care services among migrants than general populations due to restrictive health-related policies, poor economic conditions, and the lack of awareness of seeking medical services [ 36 , 37 ]. Migrants were often overlooked for the RV vaccine catch-up immunization programs and their immunity was often acquired by natural infection [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the accelerating urbanization in China, a large number of the rural adult labor force are leaving their hometowns and choosing to work and settle in cities [ 53 , 54 ]. Although the substantive size of the family network had been reduced by the mobility of adult children, its role was still influential, and the friend network was not a substitute [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study found that migrant women had a lower vaccination rate of RV and were more prone to have a past infection of RV by natural ways. Previous studies have reported the insu cient utilization of health care services among migrants than general populations due to restrictive health-related policies, poor economic conditions, and the lack of awareness of seeking medical services [32,33]. Migrants were often overlooked for the RV vaccine catch-up immunization programs and their immunity was often acquired by natural infection [34].…”
Section: Migrant Status and Torch Infectionsmentioning
confidence: 99%